Cellular signaling and epigenetic regulation of gene expression in leukemia. (January 2020) - Gowda, Chandrika; Song, Chunhua; Ding, Yali; Iyer, Soumya; Dhanyamraju, Pavan K; McGrath, Mary; Bamme, Yevgeniya; Soliman, Mario; Kane, Shriya; Payne, Jonathon L.; Dovat, Sinisa
Abstract: Alterations in normal regulation of gene expression is one of the key features of hematopoietic malignancies. In order to gain insight into the mechanisms that regulate gene expression in these diseases, we dissected the role of the Ikaros protein in leukemia. Ikaros is a DNA-binding, zinc finger protein that functions as a transcriptional regulator and a tumor suppressor in leukemia. The use of ChIP-seq, RNA-seq, and ATAC-seq—coupled with functional experiments—revealed that Ikaros regulates both the global epigenomic landscape and epigenetic signature at promoter regions of its target genes. Casein kinase II (CK2), an oncogenic kinase that is overexpressed in leukemia, directly phosphorylates Ikaros at multiple, evolutionarily-conserved residues. Phosphorylation of Ikaros impairs the protein's ability to regulate both the transcription of its target genes and global epigenetic landscape in leukemia. Treatment of leukemia cells with a specific inhibitor of CK2 restores Ikaros function, resulting in cytotoxicity of leukemia cells. Here, we review the mechanisms through which the CK2-Ikaros signaling axis regulates the global epigenomic landscape and expression of genes that control cellular proliferation in leukemia.